Efektivitas Aplikasi Quizizz sebagai Media Evaluasi Pembelajaran dalam Analisis Teks Iklan Kelas VIII MTs. Al Hikmah Parombean - Muh. Hasriadin; Usman Usman; Abdul Haliq (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to determine the effectiveness of the Quizizz application as a learning evaluation medium in the analysis of advertising text in class VIII MTs. Al Hikmah Parombean. This study uses a quantitative design with a post-test only control group design method. The research subjects consisted of two classes, namely the experimental class that used the Quizizz application in learning evaluation, and the control class that did not use the application. The instrument used was in the form of multiple-choice test questions. The results of the data analysis showed that the average score of students in the experimental class was 81.38, while in the control class it was 68.33. The percentage of learning completeness in the experimental class reached 77.78%, higher than the control class which was only 38.89%. The results of the hypothesis test using independent samples t-test showed a significance value of 0.018 < 0.05, which means that there is a significant difference between the two classes. The average score of students in the experimental group was 13,056 points higher than the control group, which showed that the use of the Quizizz application was effective as an evaluation medium for advertising text analysis material in grade VIII students of MTs. Al-Hikmah Parombean.